MASALAH RISIKO DALAM PERJANJIAN PENDAHULUAN JUAL BELI RUMAH PADA PENGEMBANG PERUMAHAN PT. EMBUN PAGI BERSERI DI SAMARINDA - Teguh Mulyanta (Journal of Law ( Jurnal Ilmu Hukum ), 2017)
ABSTRACT Regarding the effort of implementation of preliminary agreement in PT. Morning Cloudy So far, both parties and the second party have tried to exercise their rights and obligations respectively. Concerning the preliminary agreement in the sale and purchase of this house is generally based on article 1338 Civil Code which states "All legally-made agreements act as laws for those who make them. The agreements can not be withdrawn other than by mutual agreement, or For reasons which by law are sufficient for that Agreements shall be carried out in good faith. In particular, the preliminary agreement is set forth in the Decree of the Minister of State for Public Housing No. 09 / KPTS / M / 1995 on Guidelines on the Sale and Purchase of Houses. The Ministerial Decree does not explicitly state the definition of the preliminary agreement, but it can only be concluded that the preliminary agreement is Agreement made before the house is completed.Settlement efforts taken in the event of default in the implementation of preliminary agreement between PT. Morning Creditor with buyer is as follows: If the preliminary agreement is void, for the un-built house, the second party (the consumer) is subject to a fine of 5% (five per cent) of the house price; Whereas if the house has been built, the second party is liable to a fine of 10% (ten per cent) of the total price of the house; In the event that the second party is late in performing its obligations, ie paying the mortgage, then before the first party decides that the second defaults, the first party first gives a warning letter to the second party up to 3x (three times). If 3x (three times) is given a warning but the second party does not heed it, then the first party has the right to decide and declare that the second party is defaulted and entitled to request a settlement under the agreement / law; In the event that the consumer cancels the purchase of the house, then the consumer must make a statement of cancellation of the purchase of the house.